Kinerja Keuangan Sebelum dan Sesudah IPO: Studi Kasus pada PT. Garuda Indonesia (Persero) - Husaini Husaini; Safrizal Effendi (Jurnal Visioner & Strategis, 2021)
This study aims to determine the differences in the financial performance of company before and after the Initial Public Offering (IPO) at PT Garuda Indonesia. The financial ratios used are CR, QR, DAR, DER, ROA, and ROE. This study uses secondary data in the form of annual financial statements from 2009 to 2018 accessed on www.idx.co.id and www.garuda-indonesia.com. The method of data analysis used is the Paired Sample T-Test using SPSS 25. The results showed that financial performance measured by six financial ratios, consisting of CR, QR, DAR, DER, ROA, and ROE are not significantly different after IPO compared to before the IPO. The IPO strategy has not been fully achieved because the financial performance conditions after the IPO have not improved. Suggestions for further research are to add more financial ratios and include PT Garuda Indonesia subsidiaries engaged in air transportation to get more accurate results